2009
DOI: 10.1016/j.jtcvs.2008.11.060
|View full text |Cite
|
Sign up to set email alerts
|

Retaining perivascular tissue of human saphenous vein grafts protects against surgical and distension-induced damage and preserves endothelial nitric oxide synthase and nitric oxide synthase activity

Abstract: The success of the saphenous vein used as a bypass graft is affected by surgical trauma and distension. Veins removed with minimal damage exhibit increased patency rates. We show that retention of perivascular tissue on saphenous vein prepared for coronary artery bypass surgery by the "no touch" technique protects against distension-induced damage, preserves vessel morphology, and maintains endothelial nitric oxide synthase/nitric oxide synthase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 34 publications
(39 reference statements)
2
82
0
Order By: Relevance
“…Morphometric analysis of the vessel wall and ultrastructural analysis using electron microscopy revealed a significant reduction in the total area of vasa vasorum in the media (P=0.007) and adventitia (P=0.014) of CT veins. Dashwood et al [6] conducted a cohort study where in both techniques a portion of the vein was distended. They studied 26 patients analysing the distension-induced morphological damage and eNOS expression.…”
Section: Resultsmentioning
confidence: 99%
“…Morphometric analysis of the vessel wall and ultrastructural analysis using electron microscopy revealed a significant reduction in the total area of vasa vasorum in the media (P=0.007) and adventitia (P=0.014) of CT veins. Dashwood et al [6] conducted a cohort study where in both techniques a portion of the vein was distended. They studied 26 patients analysing the distension-induced morphological damage and eNOS expression.…”
Section: Resultsmentioning
confidence: 99%
“…As a method to avoid over-handling of the vein and increased distention pressures a pedicle technique was developed and named the "no touch" technique. It was thought that veins procured in this manner would eliminate the need for conduit distention and its associated morbidities since the perivascular adipose tissue surrounding the vein was left intact [9]. It had been shown that this surrounding tissue in internal thoracic mammary arteries provided a vasodilatory effect with less arterial conduit vasospasm.…”
Section: How Vein Harvesting Methods Can Affect Patency Ratesmentioning
confidence: 99%
“…It had been shown that this surrounding tissue in internal thoracic mammary arteries provided a vasodilatory effect with less arterial conduit vasospasm. Increased patency rates were demonstrated with the "no touch" technique compared to the conventional open technique [9]. 1997 began a new era in coronary artery bypass grafting with the use of EVH to harvest the saphenous vein.…”
Section: How Vein Harvesting Methods Can Affect Patency Ratesmentioning
confidence: 99%
“…In the "in touch' technique of removal of the saphenous vein developed by Dashwood et al [8], maintaining a thick pedicle of the saphenous vein, mimicking the classic way of dissecting the ITA, was accompanied by greater saphenous vein patency, perhaps because of greater local release of nitric oxide. The advantage of thick pedicle is not shown in the ITA, in which there is migration in order to perform the dissection using the skeletonized technique.…”
Section: See Also Original Article On Pages 617-623mentioning
confidence: 99%